IR-UV Double Resonance Spectrum of Acetylene Below and Above the Predissociation Threshold. Issue 1 (1994) - Fujii, Masaaki; Tanabe, Shigeki; Okuzawa, Yasuo; Ito, Mitsuo
Abstract : The Ã 1 Au ←X ˜ 1 ∑ g + electronic transition of the vibrationally excited acetylene molecule was studied by IR–UV double resonance spectroscopy in gas and in a supersonic jet. The C–H antisymmetric stretching vibrationν CH ant in the Ã state was clearly observed when the molecule was excited to theν CH sym +ν CH ant combination vibration in theX ˜ state by the IR laser. When theν CH ant fundamental vibration was excited, the C–H in-plane cis-bending vibration νcis (in) in the Ã state was observed strongly, whileν CH ant almost disappeared. The difference was interpreted in terms of Fermi resonance of theν CH ant fundamental vibration inX ˜ . The predissociation threshold was newly determined to be 46, 439˼46, 673 cm -1 (133.11 ± 0.33 kcal/mol). In the region above the predissociation threshold, strong vibrational mixing was found. The higher members of the progression of the trans-bending vibration starting fromν CH ant were assigned. It was suggested that the nonradiative relaxation accelerated in the region above 51, 744 cm -1 .